Okta for good : pursuing innovation and impact in corporate social responsibility - Isaacs, Andrew M., (SAGE Business Cases., 2019)
Okta, a leader in identity and access management (IAM) software based in San Francisco, CA, has developed a unique and ambitious model for Corporate Social Responsibility (CSR). The founders demonstrated high-level commitment by setting aside equity for CSR pre-IPO. In only a few years, Okta has created a solid framework for social impact and given generously to its global communities while keeping its social impact in sync with its core business. Going forward, Okta is considering how to sustain social impact during economic downturns, grow its employee volunteer programs, and evolve its CSR model as the company matures. The model was inspired by Pledge 1%, a framework for corporate philanthropy adopted by thousands of companies around the world, guiding them to give 1% of their profit, product, and people's time toward charitable causes.